Retinoic acid as a teratogen: IX-Induction of fetal skeletal anomalies and alteration in the utero-placental expression pattern of EGFR during mice development. Issue 1 (31st December 2022) - Said, Ahmed; S. Sultan, Abdel-Rahman; Ali, Reda A.; Moustafa, Mohsen A.
ABSTRACT: Retinoic acid (RA), an active metabolite of vitamin A, plays essential signaling roles in mammalian embryogenesis. Nevertheless, it has long been recognized that overexposure to vitamin A or retinoic acid causes widespread teratogenesis in rodents as well as humans. However, the mechanism of its teratogenic effect is not yet understood. Here, we examined the effects of RA on the fetal and placental development as an attempt to find the mechanism of its teratogenicity through inhibition of utero-placental development. The pregnant mice were divided into three groups: RA treated group, control treated with dimethyl sulfoxide (DMSO) group and control non-treated group. The RA treated group received 15 mg/kg RA by intraperitoneal injection from 8.5 to 11.5 gestation days. The pregnant mice were sacrificed by cervical dislocation on days 9.5, 10.5, 12.5, 13.5 and 18.5 of gestation. The uteri were isolated, and the fetuses have been exposed to morphological examination and skeletal staining. Moreover, histological and immunohistochemical studies on placenta have been done. Morphologically, we recorded a reduction in the number of implanted fetuses besides hematoma in different parts of the uteri of the RA treated animals. Furthermore, RA was found to induce decreases in fetal weight and length, as well as malformations in the tail, forelimbs and hindlimbs, which were confirmed by skeletal examination. Interestingly, RA treatment showed a decrease in the expression level of epidermal growth factor receptor (EGFR) during placenta development, especially in junctional and labyrinth zones. We concluded that high dose of RA may have a direct teratogenic effect on the fetus besides an indirect effect through modulating EGFR signal during the placenta development.